Hierarchical Bayesian method for mapping biogeochemical hot spots using induced polarization imaging. Issue 1 (29th January 2016) - Wainwright, Haruko M.; Flores Orozco, Adrian; Bücker, Matthias; Dafflon, Baptiste; Chen, Jinsong; Hubbard, Susan S.; Williams, Kenneth H.
Abstract: In floodplain environments, a naturally reduced zone (NRZ) is considered to be a common biogeochemical hot spot, having distinct microbial and geochemical characteristics. Although important for understanding their role in mediating floodplain biogeochemical processes, mapping the subsurface distribution of NRZs over the dimensions of a floodplain is challenging, as conventional wellbore data are typically spatially limited and the distribution of NRZs is heterogeneous. In this study, we present an innovative methodology for the probabilistic mapping of NRZs within a three‐dimensional (3‐D) subsurface domain using induced polarization imaging, which is a noninvasive geophysical technique. Measurements consist of surface geophysical surveys and drilling‐recovered sediments at the U.S. Department of Energy field site near Rifle, CO (USA). Inversion of surface time domain‐induced polarization (TDIP) data yielded 3‐D images of the complex electrical resistivity, in terms of magnitude and phase, which are associated with mineral precipitation and other lithological properties. By extracting the TDIP data values colocated with wellbore lithological logs, we found that the NRZs have a different distribution of resistivity and polarization from the other aquifer sediments. To estimate the spatial distribution of NRZs, we developed a Bayesian hierarchical model to integrate the geophysical and wellbore data. In addition, the resistivity images were used to estimate hydrostratigraphic interfaces under the floodplain. Validation results showed that the integration of electrical imaging and wellbore data using a Bayesian hierarchical model was capable of mapping spatially heterogeneous interfaces and NRZ distributions thereby providing a minimally invasive means to parameterize a hydrobiogeochemical model of the floodplain. Key Points: Naturally reduced zones (NRZs) are considered to be biogeochemical hot spots under floodplains We developed a noninvasive probabilistic mapping method of NRZs using induced polarization imaging This method provides a minimally invasive means to parameterize a floodplain biogeochemical model